2019
DOI: 10.5755/j01.ms.25.4.20899
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Control Parameters During Machining of LM13 Aluminum Alloy Under Dry Electrical Discharge Machining (EDM) With A Modified Tool Design

Abstract: Dry Electrical Discharge Machining (EDM) is considered as a green manufacturing process in which the liquid dielectric medium is replaced by a high velocity gas, which results improved process stability. A special tool design is adopted to find the optimum control parameters during machining of LM13 Aluminum alloy under dry EDM mode. The drilled and slotted cylindrical copper rod is used as a tool. Discharge current (I), voltage (V), pressure (P) and pulse on time (TON) are considered as varying input process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…e formation of surface cracks was due to high uctuating stresses applied during the process of machining. Similar kind of observation was reported on wire EDM machine surfaces [27][28][29][30][31].…”
Section: Field Emission Scanning Electron Microscopy (Fesem)supporting
confidence: 84%
See 1 more Smart Citation
“…e formation of surface cracks was due to high uctuating stresses applied during the process of machining. Similar kind of observation was reported on wire EDM machine surfaces [27][28][29][30][31].…”
Section: Field Emission Scanning Electron Microscopy (Fesem)supporting
confidence: 84%
“…e change in composition of the machined surface was due to the melting and solidi cation of the machined surface. Similar kind of change in composition of the workpiece was observed in previously undergone research work in wire EDM process [29,31].…”
Section: Energy Dispersion Spectroscopy (Eds)supporting
confidence: 81%
“…It was found that the material erosion rate decreased, and the electrode wear increased with an increase in reinforcing quantity in the matrix phase [15]. Some researchers [16][17][18][19] have checked the feasibility of EDM in composite materials, and their results yield that the reinforcing constituents in the matrix obstruct effective sparking and reduce matrix phase erosion.…”
Section: Introductionmentioning
confidence: 99%
“…Newly developed power source has stabilized the discharge probability. Significant research contributions [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] in the recent years are reviewed and listed in Table 1. Alam et al [26] recently reviewed optimization of WEDM parameters, in which they detailed the past published research using GRA and RSM methods.…”
Section: Introductionmentioning
confidence: 99%